A phase separation strategy for enhanced toughness self-assembly graphene-network composites. (7th July 2022) - Hostettler, Nathan; Hubert, Pascal
Abstract: The toughness of three unsaturated polyester resins modified with different quantities of polycaprolactone (PCL) and few-layer graphene microsheets was evaluated by single-edge-notch bending (SENB). The addition of PCL to the resin systems created phase-separated microstructures with different critical compositions at phase inversion (7, 15 and 16.5 wt%PCL). The addition of PCL in quantities lower than the critical compositions showed increases up to 90% in toughness. A similar effect was observed by the addition of graphene to the neat resin increasing the toughness by up to 96% with 6 wt% of graphene. The incorporation of graphene to a phase separating system was found to form a self-assembly graphene-network at the unsaturated polyester-rich phase of the microstructure. When such network showed an appreciable effect of the toughness compared to the system without the PCL (114% increase at 6 wt% graphene and 2 wt% PCL), it also positively impacted the electrical conductivity. A shift of the percolation threshold towards a lower quantity of graphene was achieved by the creation of such graphene-rich network, reducing by 2 wt% the quantity of graphene needed for conduction. Graphical abstract: Image 1